Antimicrobial sensitivity pattern and detection of antimicrobial resistance genes of E. coli isolated from respiratory tract infections in poultry - M, BAVADHARANI; RAI, TEJINDER SINGH; ARORA, ANIL KUMAR; SINGH, SATPARKASH (The Indian Journal of Animal Sciences, 2023)
The present study was conducted at College of Veterinary Science, Guru Angad Dev Veterinary and Animal Sciences University with the objective to determine the antimicrobial sensitivity pattern and anti-microbial resistance genes on E. coli isolates obtained from respiratory infection samples of poultry. A total of 115 samples were collected from different respiratory disease outbreaks from various poultry farms of Ludhiana district of Punjab. Various bacteria related to respiratory infections were isolated and E. coli was found to be in highest number among the isolated bacteria. The isolates of E. coli were confirmed by MALDI-TOF and were subjected to Kirby Bauer’s disc diffusion method to study the antimicrobial sensitivity pattern phenotypically. The isolates were also screened for the presence of six antimicrobial resistance genes associated with certain antibiotics by Polymerase Chain Reaction (PCR). All the isolates showed 100% resistance towards the antibiotics, viz. tetracycline, chlortetracycline, enrofloxacin, erythromycin, ofloxacin, tylosin, amikacin, and ciprofloxacin. This demonstrates the multidrug-resistance of the isolates. The antimicrobial resistance gene strA (60%) was found to be expressed more among the isolates followed by ere (50%), tetA (47.5%), aac-(3)-(IV) (37.5%) and blaTEM (32.5%). None of the isolate was found to have tetC gene.